Pengaruh Ekologi, Komponen Pertumbuhan, dan Komponen Hasil terhadap Produksi Tanaman Anggur: Pendekatan Multivariat Analisis SEM-PLS (Review) - TENAYA, I MADE NARKA; UTAMI, UTAMI (Agrotrop : Journal on Agriculture Science, 2015)
The Effects of Ecology, Growth and Yield Component to The Production of Grape:Multivariate Analysis Approach of SEM-PLS. The effects of the two main componentnamely ecological environment and genetic cannot be avoided during the process of growth ofplant since the early growth until it has produce yield. Ecological environment consist of soil,climate, and treatment mean while genetic mean variety of the plant. This research wasdesigned to study the effects of ecology, vegetative and gerative growth, and yield componento the production of grape. Structural Equation Modeling variance base with PLS Smart 2.0M3 was use to analysed the data. The result show that three of the four component hadsignificant effects on the production of grape, namely ecology, vegetative growth and yieldcomponens (p<0.05) mean while only generative component not has significant effects (tstatistic0.521 < 1.96). The production equation was PRODUCTION = - 0,235 KEKO + 0,243KVEGE + 0,020 KGENE + 0,417 KKHS (R2 = 63,2%).
Keywords: ecology; growth; yield component; SEM-PLS